Epoxyeicosatrienoic Acid Analog Decreases Renal Fibrosis by Reducing Epithelial-to-Mesenchymal Transition - Skibba, Melissa; Hye Khan, Md. Abdul; Kolb, Lauren L.; Yeboah, Michael M.; Falck, John R.; Amaradhi, Radhika; Imig, John D. (Frontiers in Pharmacology, 2017)
Renal fibrosis, which is a critical pathophysiological event in chronic kidney diseases, is associated with renal epithelial-to-mesenchymal transition (EMT). Epoxyeicosatrienoic acids (EETs) are Cyp epoxygenase arachidonic acid metabolites that demonstrate biological actions that result in kidney protection. Herein, we investigated the ability of 14,15-EET and its synthetic analog, EET-A, to reduce kidney fibrosis induced by unilateral ureter obstruction (UUO). C57/BL6 male mice underwent sham or UUO surgical procedures and were treated with 14,15-EET or EET-A in osmotic pump (i.p.) for 10 days following UUO surgery. UUO mice demonstrated renal fibrosis with an 80% higher kidney-collagen positive area and 70% higher α-smooth muscle actin (SMA) positive renal areas compared to the sham group. As a measure of collagen content, kidney hydroxyproline content was also higher in UUO (6.4±0.5µg/10mg) compared to sham group (2.5±0.1µg/10mg). Along with marked renal fibrosis, UUO mice had reduced renal expression of EET producing Cyp epoxygenase enzymes. Endogenous 14,15-EET or EET-A demonstrated anti-fibrotic action in UUO by reducing kidney-collagen positive area (50-60%), hydroxyproline content (50%), and renal α-SMA positive area (85%). In UUO mice, renal expression of EMT inducers, Snail1 and ZEB1 were higher compared to sham group. Accordingly, renal epithelial marker E-cadherin expression was reduced and mesenchymal marker expression was elevated in the UUO compared to sham mice. Interestingly, EET-A reduced EMT in UUO mice by deceasing renal Snail1 and ZEB1 expression. EET-A treatment also opposed the decrease in renal E-cadherin expression and markedly reduced several prominent renal mesenchymal/myofibroblast markers in UUO mice. Overall, our results demonstrate that EET-A is a novel anti-fibrotic agent that reduces renal fibrosis by decreasing renal EMT.